Theoretical and practical perspectives of diesel locomotive with DC traction motors wheel-sets’ slipping and sliding control - Liudvinavičius, Lionginas; Bureika, Gintautas (Transport, 2011)
The causes of slipping and sliding of the locomotive's driving wheel-sets are analysed from theoretical and practical perspectives. The main factors influencing wheel-sets’ slipping are described, and their correlation is determined. The specific methods of stopping the slipping of the Diesel locomotives and having a conventional electric drive system are described in the paper. The process of wheel-sets’ slipping and its control are simulated and shown graphically. Structural diagrams demonstrating the control of the dynamic locomotive wheel-sets’ slipping and sliding, based on the evaluation of the influence of the speed-torque characteristics of DC traction motors on these processes, are presented. Major parameters of the DC/DC and AC/DC systems used in the automatic control of the dynamic slipping and sliding of the locomotive's wheel-sets are defined and new methods of controlling the dynamic slipping and sliding are suggested.First Published Online: 09 Jan 2012